Transient stability enhancement of statcom integration in power grid - I. A Ethmane; A.K. Mahmoud; M. Maaroufi; A. Yahfdhou (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
To solve load growth of a hybrid existing electrical system, we at first build generation stations (wind, solar or thermical). And secondly in 2025 year, when the system is so meshed, some buses will be very far from production energy, the transits power will be lower than the transmission capacity, and the voltage drop out margin limit of stability. Therefore it is proposed to install Flexible AC Transmission System (FACTS) devices to enhance the transient power stability and quality in the power system. The power flow analysis of Newton Raphson method is performed on a seven (7) bus system with and without static synchronous compensator (STATCOM). The STATCOM is a shunt connected FACTS devices that are useful for reactive power compensation and mitigation of power quality problems in transmission and distribution systems. These investigations indicate the need of power flow analysis and determine best locations of STATCOM on the proposed system. The results of simulation have been programmed in MATLAB and PSS/E Simulator. In the end the expected disturbances and the power quality enhancement of the network in the horizon 2025 were attenuated by integration of STATCOM that is able to supply or absorb reactive power and to maintain the voltage at 1pu.